DNA Conformation Induces Adaptable Binding by Tandem Zinc Finger Proteins - Patel, Anamika; Yang, Peng; Tinkham, Matthew; Pradhan, Mihika; Sun, Ming-An; Wang, Yixuan; Hoang, Don; Wolf, Gernot; Horton, John R.; Zhang, Xing; Macfarlan, Todd; Cheng, Xiaodong (Cell, 2018)
Tandem zinc finger (ZF) proteins are the largest and most rapidly diverging family of DNA-binding transcription regulators in mammals. ZFP568 represses a transcript of placental-specific insulin like growth factor 2 (Igf2-P0) in mice. ZFP568 binds a 24-base pair sequence-specific element upstream of Igf2-P0 via the eleven-ZF array. Both DNA and protein conformations deviate from the conventional one finger-three bases recognition, with individual ZFs contacting 2, 3, or 4 bases and recognizing thymine on the opposite strand. These interactions arise from a shortened minor groove caused by an AT-rich stretch, suggesting adaptability of ZF arrays to sequence variations. Despite conservation in mammals, mutations at Igf2 and ZFP568 reduce their binding affinity in chimpanzee and humans. Our studies provide important insights into the evolutionary and structural dynamics of ZF-DNA interactions that play a key role in mammalian development and evolution. [Display omitted] •ZFP568 and its Igf2-P0 binding activity is conserved in eutheria•Mouse ZFP568 11-finger array makes numerous non-canonical ZF-DNA interactions•ZFP568 forms versatile contacts in response to sequence-specific deformation in DNA•Chimp and human ZFP568 have weakened or abolished binding to their Igf2-P0 sequence Evolutionary and structure-function dynamics of zinc finger-DNA interactions reveal unconventional recognition codes and co-evolution of ZFP568 and its target gene Igf2 in mammals.